Niat Menggunakan Aplikasi TikTok: Faktor-faktor Dominan Apa Yang Mempengaruhi? - Nur Kholifah; Nurul Azizeh; Riska Denia; Nurjana Fitri Romadhon; Vira Kurniasih; Usep Suhud (Jurnal Bisnis, Manajemen, dan Keuangan, 2021)
The goal of this study is to test the factors that influence the intention to use TikTok. There are six variables that used to measure, namely personal innovativenes, perceived ease of use, perceived risk, satisfaction, perceived enjoyment, and intention to use TikTok. Data collection was conducted during the three months from November 2020 to January 2021 using an online questionnaire. The study had 212 respondents consisting of 45 men (21.2%) and 167 women (78.8%). Exploratory factor analysis and structural equation model was used to process data. The results of this study are show that personal innovativeness has significant effect on perceived ease of use, perceived risk has no significant effect on perceived ease of use, perceived ease of use has significant effect on satisfaction, perceived ease of use has significant effect on perceived enjoyment, personal innovativeness has significant effect on intention to use TikTok, satisfaction has no significant effect on intention to use TikTok, perceived ease of use has significant effect on intention to use TikTok, perceived enjoyment has no significant effect on intention to use TikTok, and perceived risk has no significant effect on intention to use TikTok.